ANALISIS PENERIMAAN TEKNOLOGI DOMPET DIGITAL PADA UMKM DI KOTA BANDUNG - Islamiaty Ruhlfie Puteri; Candra Wijayangka (Politeknik Negeri Batam, 2020)
The industrial revolution 4.0 is influencing today's life, especially the use of smart technology which has made it easier for a variety of human activities, especially in payments using e-wallets. E-wallet is not only developed in well-known stores, but has expanded to MSMEs in Bandung. However, there are still some obstacles to the acceptance of this new technology due to various factors in the community. This study aims to determine how acceptance of Gopay and OVO E-Wallet technology in MSMEs in Bandung uses the Unified Theory of Acceptance and Use of Technology model that has variable performance expectation, effort expectation, social influence, perceived risk, perceived cost and behavioral intention. The method used in this research is descriptive and causality methods with a quantitative approach, and using a hypothesis testing technique that is the T test. The sampling method used was purposive sampling with a total of 100 respondents. Based on the results of data processing using SmartPLS obtained performance expectation, effort expectation, social influence and perceived cost significantly influence behavioral intention of 97.5%. Perceived risk is known to have no effect on this study, this can be caused by differences in the type of technology, the monetary value of the technology users use and also the reputation of the community.